The Effect Of Promotion Mix Costs On Sales Volume And Its Impact On The Benefits Of Agribusiness Medium Enterprises In Maros District - Ahmad Rijal; Ahmad Ramadhan Siregar; Jusni (Publisher Cv. Inara, 2021)
This research was conducted on Small and Medium Enterprises in the agribusiness sector in Maros Regency by taking data on the promotion mix costs, sales volume and profits from 2017-2019. The purpose of this research is to partially determine the effect of advertising costs, promotion costs, personal selling costs on sales volume in increasing profits in agribusiness Small and Medium Enterprises in Maros district. This type of quantitative research uses an associative approach which aims to determine the effect and relationship between the independent variable and the dependent variable through intervening variables. The sample in the study obtained 21 small and medium enterprises using purposive sampling technique. The data analysis technique used is regression analysis with the help of SPSS and Sobel test. The results showed that advertising costs (X1) and personal selling costs (X3) had a significant effect on sales volume in increasing profits with the calculated value of the Sobel test, the Z1 value obtained was 2.0337 and Z3 was 2.168 > 1.669 and the selling promotion costs ( X2) does not have a significant effect on sales volume in increasing profits in small and medium agribusiness enterprises in Maros district. The value of the calculation of the Sobel test, the Z2 value obtained is -0.4967 < 1.669 (t table N = 63, Prob 5%).